Computer-Based Cognitive Development Model with Reggio Emilia Approach in Kindergarten - Parwoto, Parwoto (Universitas Negeri Makassar, 2013)
The study is designed to research and development (Research and Development). Methods of data collection using questionnaire, interview, observation, and documentation. Pemerian performed at the level of the needs assessment, the content validation and empirical validation. The results of the needs assessment models in general REA PKBK-oriented game experience through the adoption of microsoft paint program, Correl draw, and adop photo is needed in schools, especially for gifted education services. Limited test and analysis results show that a class of computer-based cognitive development in Reggio Emelia approach is better than the group of children who attend conventional learning